Optimal Antiviral Treatment Strategies of HBV Infection Model with Logistic Hepatocyte Growth. (26th June 2013) - Laarabi, Hassan; Abta, Abdelhadi; Rachik, Mostafa; Bouyaghroumni, Jamal
Abstract : This study considers an optimal therapy strategy for HBV infection by incorporating two controls laws into a previous hepatitis B viral infection model with logistic hepatocyte growth. Our goal is to maximize the number of healthy cells and to minimize the cost of the therapy. In this context, the existence of an optimal control is proved. The optimal control is obtained by solving the optimality system which was composed of three nonlinear ODEs with initial conditions and three nonlinear adjoint ODEs with transversality conditions. The results were analysed and interpreted numerically using MATLAB.